Pengaruh Tayangan YouTube Channel GMMTV OFFICIAL Terhadap Minat Belajar Bahasa Thailand - Adinda Siti Nur Afifah; Mayasari Mayasari; Luluatu Nayiroh (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
YouTube is a popular social media medium of information and entertainment, and the increase of YouTube users is increasing every year. The GMMTV OFFICIAL YouTube Channel is one of the channels favored by individuals to find shows in the form of drama series, game shows, and variety shows. This study aims to determine the effect of the GMMTV OFFICIAL YouTube Channel on interest in learning Thai. This study uses new media theory with quantitative research methods through questionnaire data collection techniques with a total sample of 100 respondents. The results of this study indicate that the GMMTV OFFICIAL YouTube Channel shows interest in learning Thai language with a coefficient of determination of 49.3% and the rest is caused by other reasons. Through the results of research that has been processed with SPSS 26, the interactivity of the GMMTV OFFICIAL YouTube Channel has no significantly effects an interest in learning Thai. The flexibility of the GMMTV OFFICIAL YouTube Channel has significantly effect an interest in learning Thai. Media exposure to GMMTV OFFICIAL's YouTube Channel has significantly effect an interest in learning Thai. Keywords: YouTube, Interest in learning, Thai Language